Comparison of the effects of several potassium-channel openers on rat bladder and rat portal vein in vitro - Edwards, G; Henshaw, M; Miller, M; Weston, A H (British journal of pharmacology, 1991)
1. The ability of several K-channel openers to inhibit KCl-induced contractions of rat bladder detrusor and spontaneous mechanical activity in rat portal vein was examined. 2. Lemakalim, pinacidil, Ro 31-6930, RP 49356, P1060 and S 0121 dose-dependently relaxed rat detrusor, precontracted with 20 mM KCl. With the exception of pinacidil, concentrations of these agents below 30 microM did not inhibit 80 mM KCl-included contractions. Pinacidil (10 microM) produced a small, but significant (P < 0.05) relaxation of 80 mM KCl-induced mechanical activity. Minoxidil sulphate and BRL 38226 produced some relaxation of 20 mM but not 80 mM KCl-induced contractions. 3. Glibenclamide (0.3-3 microM) antagonized the relaxant effects of lemakalim, pinacidil, Ro 31-6930, RP 49356, P1060 and S 0121 in a competitive manner (pA2 values 6.3-6.6). The effects of minoxidil sulphate and BRL 38226 were fully antagonized by 3 microM glibenclamide. 4. Lemakalim, pinacidil, S 0121, BRL 38226 and minoxidil sulphate were each approximately 8 times more potent as inhibitors of the spontaneous contractions of rat portal vein than KCl-induced contractions of the rat detrusor. Minoxidil sulphate was approximately 30 times more potent in the rat portal vein than in the bladder. This may indicate that either minoxidil sulphate is acting at different recognition sites in these two tissues, or that this compound has an additional mechanism of action in the portal vein. 5. With the exception of minoxidil sulphate, all the compounds tested stimulated 86Rb efflux and 42K efflux from preloaded rat detrusor strips. The stimulated 86Rb efflux was qualitatively but not quantitatively similar to the stimulated 42K efflux. Minoxidil sulphate stimulated 42K efflux from rat portal vein but not from rat bladder. 6. It is concluded that all the compounds tested cause relaxation of rat detrusor predominantly by Kchannel opening. Selectivity for bladder rather than vascular smooth muscle was not shown by any compound.